KARAKTERISTIK TANAH PADA LAHAN AGROFORESTRI TANAMAN RAJUMAS (Duabanga moluccana), KLOKOS (Eugenia sp) DAN JUKUT (Eugenia polyantha) DI KAWASAN RARUNG LOMBOK TENGAH - Eviani, Sri; Suwardji, Suwardji; Priyono, Joko (Journal of Soil Quality and Management, 2024)
During the 28 years of implementing agroforestry in Rarung Forest, Lombok Tengah, a research study was conducted to examine the soil characterization in the agroforestry plots of Rajumas (Duabanga moluccana), Klokos (Eugenia sp), and Jukut (Eugenia polyantha). The research method used was a descriptive method with survey techniques. Three agroforestry systems were studied: Rajumas agroforestry, Klokos agroforestry, and Jukut agroforestry. Soil samples were taken from each soil profile layer beneath the respective land uses.The research was conducted in July-August 2022, at the Rarung Forest area in Central Lombok, and the soil analysis was performed at the Soil Physics and Conservation Laboratory and the Soil Chemistry and Biology Laboratory, Faculty of Agriculture, Mataram University. Three parameters were tested: soil physical properties (soil bulk density, soil particle density, porosity, and soil texture), soil chemical properties (soil pH, organic carbon, total nitrogen, and cation exchange capacity), and soil biological properties (CO2 evolution).The results of the study showed that the soil properties varied among all land use systems. Over the 28-year period, the Rajumas agroforestry system had the best soil quality in terms of physical and chemical properties, while the Klokos agroforestry system exhibited rapid soil CO2 evolution in terms of biological properties